Dari Cinta Ke Luka: Analisis Dampak Kekerasan Verbal Terhadap Kondisi Psikologis Pasangan Suami Istri - Imayanti, Lilis; Putri Sabrina, Karissa; Aurielle Shevanka, Keyra; Afifah, Muthia; Siti Fawziyah, Kalila; Ferizal, Muhammad; Whilky Rizkyanfi, Mochamad (Jurnal Consulenza : Jurnal Bimbingan Konseling dan Psikologi, 2025)
Verbal abuse in domestic settings is a form of psychological violence that causes serious harm to the mental well-being of victims, both women and men. However, this form of violence is often overlooked due to its non-physical nature and the ongoing social stigma surrounding it. This study aims to explore the characteristics of verbal abuse, its causal factors, psychological impacts on victims, and the reasons victims remain in abusive relationships. A literature review method was employed, analyzing scientific articles published within the last five years from national and international databases. The findings reveal that verbal abuse leads to depression, anxiety, diminished self-esteem, and long-term psychological trauma. Contributing factors include the perpetrator’s personality traits, childhood experiences, power imbalances, and patriarchal culture. Victims tend to remain in abusive relationships due to social pressure, economic dependence, and false hope of change. This study concludes that verbal abuse should be understood as a form of symbolic domination that erodes the victim’s self-concept. The scholarly contribution of this research lies in its psycholinguistic approach, which highlights the role of language as a tool of power and violence in intimate relationships.